The effect of follicular fluid-related hormones and vascular endothelial factor levels on the formation of high-quality embryos - Lin Liang; Xiao Xi Zhao (Clinical and Experimental Obstetrics & Gynecology)
Background: The purpose of this study was to investigate the possible influence of follicular fluid (FF)-related hormones and vascular endothelial factor (VEGF) levels on oocytes, and the resulting effect on formation of high-quality embryos, to provide a scientific basis for improving controlled ovarian stimulation. Methods: The levels of hormones and VEGF in FF were determined by performing enzyme-linked immunoassays. According to the number of high-quality embryos obtained, the patients were divided into three groups, and the levels and constitution of hormones and VEGF in FF were compared. Based on the results of correlation analysis, the number of oocytes harvested and the concentration of follicle-stimulating hormone (FSH) in FF were substituted into multiple logistic regression models. Results: The number of high-quality embryos was negatively correlated with FSH concentration (correlation coefficient = -0.305, p = 0.0001). The concentration of VEGF, FSH, luteinising hormone, and estradiol in FF was significantly different among the different high-quality embryo number groups. Multiple logistic regression results showed that the FSH concentration in the FF of the group without embryos was significantly higher than that of the other two groups, and the number of eggs obtained in the third group was significantly higher than that of the group without embryos. Conclusion: In the late stage of follicular development, FSH concentration in FF and the number of oocytes obtained affects the formation of high-quality embryos.